An index of the economic dependence on tourism. - Ortega-Aguaza, Bienvenido; Ribeiro, Manuel Alector (Sage, 2024)
This study proposes a methodology to construct a Tourism Economic Dependence Index for a sample of 144 countries spanning the period 1995–2019. This index aims to serve as a summary measure of countries’ dependence on tourism while controlling for differences in economic development levels across countries. Findings suggest that an index value of 20% may be considered a threshold for identifying highly tourism-dependent countries. Furthermore, the results of the index indicate that economies have experienced a slight trend toward higher levels of dependence on tourism since the global financial crisis. However, estimates from a panel convergence model suggest that the hypothesis of convergence toward a common long-run equilibrium in index levels across countries can be rejected. Instead, different groups of countries converging toward the same long-run equilibrium level of the index have been identified.
https://openpolicyfinder.jisc.ac.uk/id/publication/13304
Keywords: Riqueza; Turismo; Análisis de datos de panel; Club convergence; Composite index; Country-level analysis; Economic dependence on tourism; Panel data